Profitability and Product Quality: Economic Determinants of Airline Safety Performance - Rose, Nancy L. (Journal of Political Economy, 1990)
This study investigates product safety choices in the airline industry, with particular attention to the role of financial conditions. The analysis uses data on 35 large scheduled passenger airlines over the 1957-86 period to estimate the effect of profitability and other aspects of financial health on accident and incident rates. The results indicate that lower profitability is correlated with higher accident and incident rates, particularly for smaller carriers. These findings support a broad class of theoretical models that suggest links between financial conditions and product quality and may have significant implications for the allocation of safety inspection and enforcement resources.